2020
DOI: 10.1099/ijsem.0.004290
|View full text |Cite
|
Sign up to set email alerts
|

Polaribacter septentrionalilitoris sp. nov., isolated from the biofilm of a stone from the North Sea

Abstract: A new member of the family Flavobacteriaceae was isolated from the biofilm of a stone at Nordstrand, a peninsula at the German North Sea shore. Phylogenetic analysis of the 16S rRNA gene sequence showed that strain ANORD1 T was most closely related to the validly described type strains Polaribacter porphyrae LNM-20 T (97.0 %) and Polaribacter reichenbachii KMM 6386 T (96.9 % 16S rRNA gene sequence similarity) and clustered with Polaribacter gangjinensis K17-16 T (96.0 %). Strain ANORD1 T was determined to be m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Marinomonas species are abundant in seawater (Ivanova et al, 2005 ; Yoon et al, 2005 ) and were highly abundant in the microbial community of rotifer cultures prepared as a feed for fish larvae (Rombaut et al, 2001 ). Polaribacter species have been isolated from Antarctic soil and in biofilms on stones from the North Sea (Choo et al, 2020 ; Kim et al, 2013 ), and the genus was detected in the intestine of marine organisms and algae (Hyun et al, 2014 ; Nedashkovskaya et al, 2013 ; Wei et al, 2018 ). Alkalimarinus sediminis was isolated from marine sediment in Shandong Province, China (Zhao et al, 2015 ), and Alkalimarinus species were found in bone‐eating worms ( Osedax mediterranea ) from the Mediterranean Sea (Hewitt et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Marinomonas species are abundant in seawater (Ivanova et al, 2005 ; Yoon et al, 2005 ) and were highly abundant in the microbial community of rotifer cultures prepared as a feed for fish larvae (Rombaut et al, 2001 ). Polaribacter species have been isolated from Antarctic soil and in biofilms on stones from the North Sea (Choo et al, 2020 ; Kim et al, 2013 ), and the genus was detected in the intestine of marine organisms and algae (Hyun et al, 2014 ; Nedashkovskaya et al, 2013 ; Wei et al, 2018 ). Alkalimarinus sediminis was isolated from marine sediment in Shandong Province, China (Zhao et al, 2015 ), and Alkalimarinus species were found in bone‐eating worms ( Osedax mediterranea ) from the Mediterranean Sea (Hewitt et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%